Prevalence and severity of temporomandibular joint disorders among house officers & post-graduate residents of private & public sector medical hospitals in Peshawar, Pakistan - Mohammad Ilyas; Fariha Kifayat; Faryal Gul; Salman Khan; Sumaira Saeed; Adam Khan Danish (Gandhara University, 2019)
OBJECTIVES: To evaluate the prevalence and severity of TMDs in house officers and postgraduate students belonging to public and private sector medical and dental colleges. METHODOLOGY: This was a cross sectional study carried out from July 2018 to September 2018 in Department of Oral and Maxillofacial Surgery, Sardar Begum Dental College and Hospital, Peshawar. After approval from ethical committee Gandhara University, an informed consent was obtained and Fonseca questionnaire was used to evaluate TMDs from 320 subjects who voluntarily want to participate in the study; selected with equal genders from public and private sectors medical and dental hospitals, Peshawar. Those who have musculoskeletal, neurological, systemic problems and orthodontics treatment subjects were excluded from the study. RESULTS: The age range selected was 22-32 years and the mean age presentation was 26.5 ± 3.4 years. Results showed that female postgraduate residents of private sector consider themselves tenser (18.8%) than others. 70.17% female house officers of private sector have noticed TMJ clicking and 83.17% of male house officers clenched or grind their teeth than others. CONCLUSION: The study concluded that mild and moderate TMDs are more common in-house officers and postgraduate residents. KEYWORDS: Temporomandibular Disorders, Prevalence, Temporomandibular Joint, Fonseca's Anamnestic Index, Cross-Sectional Study